Application of Adaptive Neuro-fuzzy inference System in Performance-based Condition Monitoring of Industrial Gas Turbines - BOURIAABADI, MOHAMMADREZA TAHAN (2017)
This thesis provides a detailed investigation on performance-based data-driven automatic condition monitoring of industrial gas turbine engines for fault detection, isolation and prognosis to improve the maintenance strategy of this critical equipment.